Pelatihan Strategi Peningkatan Motivasi SDM Berdaya Saing Global - Bambang Ismaya (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
This community service intends to prepare the quality of Human Resources who are able to compete in order to achieve quality levels from all aspects and can work professionally and this activity is carried out in the West Kerawang sub-district, Kerawang Regency. Method; The programs implemented are the following activities. Results: From this activity, several contributions were made as follows: the creation of an understanding of the meaning of quality education among the community, the realization of the local government's commitment to realizing quality education to meet the needs and demands of its citizens and other stakeholders, building public awareness to actively participate in realizing education globally competitive. Conclusion; This activity resulted in several contributions to the creation of an understanding of the meaning of quality education with global competitiveness among citizens. Realization of government commitment. Public awareness to actively participate in realizing quality education with global competitiveness. The formation of a community mindset in economic and social independence in realizing a globally competitive education